THE PLACE OF FOLK MUSICAL INSTRUMENTS IN THE DIPLOMACY AND MILITARY HISTORY OF THE KYRGYZ PEOPLE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The scientific article examines the role of folk musical instruments in the diplomatic and military history of the Kyrgyz people. The article’s primary goal is to describe the role of individual types of folk musical instruments in Kyrgyz diplomatic relations and military history using the epic “Manas” as an example. For instance, the first part of the study is devoted to the history of Kyrgyz wind musical instruments such as the “trumpet, horn, zheznay, chimyldak, choor, sybyzgy, chynyroo”, and then the attention is focused on the folk percussion instrument called “dobulbas” etc.
Keywords: Folk musical instruments, Kyrgyz diplomacy, military history, epic “Manas”.